Protection of property rights of spouses according to ukrainian and European Union legislations - Oksaniuk, Oleg; Vatras, Volodymyr; Havrik, Roman; Levkivskiy, Bogdan; Lohvinova, Mariia (DIXI, 2024)
Introduction: The protection of spouses’ property rights stands as a fundamental aspect within family law, aiming to safeguard their interests during property disputes and divorce proceedings. This study delves into the nuances of property rights protection under both Ukrainian and EU legal frameworks. Emphasizing the evolving legal landscape due to Ukraine’s alignment with EU standards, the research scrutinizes the mechanisms governing property division and dispute resolution. Methodology: Amidst the complexities of divorce proceedings, the analysis reveals disparities between Ukrainian legislation and established European legal norms. Despite efforts to align with EU standards, discrepancies persist, influenced by unique legal structures and societal factors. Notably, the study underscores the pivotal role of marriage contracts and judicial interventions in safeguarding spouses’ property rights. Results: Recognizing the centrality of property rights within family law, the study advocates for enhanced attention to the harmonization of Ukrainian legislation with EU principles. The efficacy of marriage contracts emerges as a cornerstone in empowering spouses to assert control over property matters. Conclusions: Additionally, the research illuminates pathways for protecting family rights through contractual agreements and legal mechanisms, underscoring the imperative of comprehensive legal reforms to ensure equitable property division.